2023
DOI: 10.1002/jor.25682
|View full text |Cite
|
Sign up to set email alerts
|

The biointegration profile of fiber‐reinforced plates following tibial implantation in sheep

Nicolette D. Jackson,
Abraham Nyska,
Ezequiel Palmanovich
et al.

Abstract: Bio‐integrative, mineral fiber‐reinforced bone fixation implants recently introduced in orthopedic surgery have expanded available treatment options for fractures and bone deformities. This new technology aims to address the disadvantages of permanent metallic implants while overcoming inherent concerns of adverse inflammatory reactions when using polymer‐based orthopedic implants. The purpose of this double‐arm preclinical study was to evaluate the safety, biocompatibility and bio‐integration of fiber‐reinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Previously published preclinical studies for ber reinforced implants demonstrate a similar cellular response observed in this study dominated by a non-destructive phagocytic response during polymer degradation 54,55 . The cellular response at all sites was characterized by non-in ammatory M2-like macrophages and MNGCs, with peak bioabsorption at 52W to 104W.…”
Section: Discussionsupporting
confidence: 80%
“…Previously published preclinical studies for ber reinforced implants demonstrate a similar cellular response observed in this study dominated by a non-destructive phagocytic response during polymer degradation 54,55 . The cellular response at all sites was characterized by non-in ammatory M2-like macrophages and MNGCs, with peak bioabsorption at 52W to 104W.…”
Section: Discussionsupporting
confidence: 80%
“…A new generation of materials is emerging with more of a focus on mimicking the biological, topographic, and bioactive features of the native tissue, such as the natural niche in which stem cells reside. Prominent examples include regenerative periodontal bioactive materials [1], skin-mimicking hydrogel dressings for advancing wound care [2], and enhancements for cellular integration in bone structural repairs [3]. In ophthalmology, biomaterials play a key role both surgically-in the form of stitches-and remedially (as contact lenses).…”
Section: Introductionmentioning
confidence: 99%